Access to non-pecuniary benefits: does gender matter? Evidence from six low- and middle-income countries - Alfano Marco; Gupta Neeru (BMC, 2011)
Abstract Background Gender issues remain a neglected area in most approaches to health workforce policy, planning and research. There is an accumulating body of evidence on gender differences in health workers' employment patterns and pay, but inequalities in access to non-pecuniary benefits between men and women have received little attention. This study investigates empirically whether gender differences can be observed in health workers' access to non-pecuniary benefits across six low- and middle-income countries. Methods The analysis draws on cross-nationally comparable data from health facility surveys conducted in Chad, Côte d'Ivoire, Jamaica, Mozambique, Sri Lanka and Zimbabwe. Probit regression models are used to investigate whether female and male physicians, nurses and midwives enjoy the same access to housing allowance, paid vacations, in-service training and other benefits, controlling for other individual and facility-level characteristics. Results While the analysis did not uncover any consistent pattern of gender imbalance in access to non-monetary benefits, some important differences were revealed. Notably, female nursing and midwifery personnel (the majority of the sample) are found significantly less likely than their male counterparts to have accessed in-service training, identified not only as an incentive to attract and retain workers but also essential for strengthening workforce quality. Conclusion This study sought to mainstream gender considerations by exploring and documenting sex differences in selected employment indicators across health labour markets. Strengthening the global evidence base about the extent to which gender is independently associated with health workforce performance requires improved generation and dissemination of sex-disaggregated data and research with particular attention to gender dimensions.